2011
DOI: 10.1186/1742-2094-8-10
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for regulatory diversity and auto-regulation at the TAC1 locus in sensory neurones

Abstract: The neuropeptide substance-P (SP) is expressed from the TAC1 gene in sensory neurones where it acts as a key modulator of neurogenic inflammation. The promoter of TAC1 (TAC1prom) plays a central role in the regulation of the TAC1 gene but requires the presence of a second regulatory element; ECR2, to support TAC1 expression in sensory neurones and to respond appropriately to signalling pathways such as MAPkinases and noxious induction by capsaicin. We examined whether the effect of capsaicin on ECR2-TAC1prom a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…Using these cells, we were unable to show that GAL5.1 could act as an enhancer of promoter activity. However, we have previously shown that many regulatory sequences are only able to act as enhancers in response to activation of an appropriate signal transduction cascade (Shanley et al, 2010(Shanley et al, , 2011. Thus, we were able to show that GAL5.1 acted as an enhancer of promoter activity following activation of the PKC pathway, which is known to modulate gene expression in the hypothalamus and amygdala, but not PKA or MAPkinase pathways.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Using these cells, we were unable to show that GAL5.1 could act as an enhancer of promoter activity. However, we have previously shown that many regulatory sequences are only able to act as enhancers in response to activation of an appropriate signal transduction cascade (Shanley et al, 2010(Shanley et al, , 2011. Thus, we were able to show that GAL5.1 acted as an enhancer of promoter activity following activation of the PKC pathway, which is known to modulate gene expression in the hypothalamus and amygdala, but not PKA or MAPkinase pathways.…”
Section: Discussionmentioning
confidence: 72%
“…ECR2 could only drive tissue-specific expression in the presence of the endogenous TAC1 promoter whereas GAL5.1 can support expression in the presence of an exogenous weak promoter such as the human b-globin promoter or HSV-TK promoter. These observations suggest that different enhancers possess varying levels of autonomy or interdependence and that the GAL5.1 is functionally self-contained relative to some other previously characterized enhancers (Shanley et al, 2010(Shanley et al, , 2011.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Alternatively, LPS can directly modulate pulpal afferents. TLR4 is expressed in a subpopulation of dorsal root ganglia neurons that contain substance P (Shanley et al, 2011). Moreover, CD14 and TLR4 are expressed in pulpal afferent terminals and trigeminal nociceptors, mainly in a TRPV1-positive subpopulation (Wadachi and Hargreaves, 2006;Diogenes et al, 2011;Ferraz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted using the isolate II RNA minikit (Bioline). Quantitative reverse transcriptase-PCR (QrtPCR) to determine mRNA expression levels of genes flanking mGAL5.1 ( Lrp5, Ppp6r3, Gal, Mlt5 and Cpt1a ) was undertaken using gene specific primers (See table 1 in supplementary data) on derived cDNA using mouse Qrt-PCR primers as previously described 19, 20 using a Roche Light Cycler 480 with Roche SYBR green. All QrtPCR analyses were normalised using mouse primers specific to the Nono housekeeping gene that gave the most stable expression in all neuronal tissues analysed compared to βactin, HPRT or GAPDH genes.…”
Section: Methodsmentioning
confidence: 99%